Gearing towards efficiency and efficacy in the planning of Medical Arts buildings a look into selected Metro Manila hospitals - Jose, John Ernest F.
In this thesis, the researcher analyzed eight different Medical Arts buildings in Metro Manila regarding their physical comfort, space efficiency, and legibility. The study argues that effective and efficient space planning can improve patient care. The findings of the study also aim to organize a body of knowledge that researchers, hospital architects, and hospital administrators can utilize in formulating a formal standard or assessment tool in designing Medical Arts Buildings or Outpatient care facilities. The study was deemed significant due to the growing number of hospital constructions, largely due to the enactment of the Universal Health Care Bill. The growing economy, an increasing population demanding better healthcare, and changes in medical technology advancements were also considerations as to why Medical Arts facilities are now common. While the study does not aim to become a standard on how Medical Arts Building should be designed, it provides a glimpse on how current Medical Arts Facilities were designed and through finding their strengths and weaknesses, a standard or rule of thumb can be made of identified through further studies. The data-gathering activities included examining floor plans, researching of existing studies on hospital design, interviewing hospital architects, and visiting selected hospitals in Metro Manila to access the physical comfortability, directness, and presence of waymaking on the project. The study was able to rank these hospitals on how they fare on the different criteria set on the study, and gives in-depth analysis on the results. The study concludes that by statistical analysis and floor plan review, the Medical Arts Buildings are significantly different from one another in terms of comfortability, directness, density, and legibility. In addressing the strengths and weaknesses of the eight hospitals included in the study, future hospitals can use these learnings to build better Medical Arts building in the future. Finally, the researcher gave architectural and managerial recommendations that could help improve future Medical Arts Building design.